2014
DOI: 10.1016/j.vaccine.2014.08.033
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and antigenic characterisation of serotype A FMD viruses from East Africa to select new vaccine strains

Abstract: Vaccine strain selection for emerging foot-and-mouth disease virus (FMDV) outbreaks in enzootic countries can be addressed through antigenic and genetic characterisation of recently circulating viruses. A total of 56 serotype A FMDVs isolated between 1998 and 2012, from Central, East and North African countries were characterised antigenically by virus neutralisation test using antisera to three existing and four candidate vaccine strains and, genetically by characterising the full capsid sequence data. A Baye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 35 publications
2
40
0
Order By: Relevance
“…Recent work has investigated the relative antigenic significance of epitopes in African serotype A FMDVs (Bari et al, 2015). These data lead on from previous research by the same group that showed existing serotype A vaccine strains protected against only 5-46% of 56 East African field strains assessed and enabled identification of a candidate strain with broader vaccine match (Bari et al, 2014).…”
Section: Novel Vaccinesmentioning
confidence: 98%
“…Recent work has investigated the relative antigenic significance of epitopes in African serotype A FMDVs (Bari et al, 2015). These data lead on from previous research by the same group that showed existing serotype A vaccine strains protected against only 5-46% of 56 East African field strains assessed and enabled identification of a candidate strain with broader vaccine match (Bari et al, 2014).…”
Section: Novel Vaccinesmentioning
confidence: 98%
“…Sudan (2011), Eritrea (2007–2009) and Egypt (2012) have reported FMDV A/Africa/G‐IV. Vaccine matching studies suggest that there is a need for reformulation of FMDV A serotype commercial vaccines in this region that currently uses A‐KEN‐05‐1980 and A‐ETH‐06‐2000 antigens (WRLFMD, –; Negusssie et al., ; Tekleghiorghis et al., ; Bari et al., ; Wekesa et al., ).…”
Section: Endemic Pools In Africamentioning
confidence: 99%
“…Although FMD can be controlled in smallholder systems, in parts of Southern Africa the presence of endemically infected wildlife makes control more challenging. In addition, although the effectiveness of vaccination programmes is an issue in many FMD‐endemic countries, this is particularly so for SAT‐2 strains that circulate in Southern Africa (Thomson et al., ; Bastos et al., ; Doel, ; Bari et al., ; Knight‐Jones et al., ). Where zonal FMD‐freedom has been achieved in Southern Africa, an ongoing threat of new outbreaks results in burdensome restrictions and periodic epidemics with suspension of beef exports (Barnes, ; Cassidy et al., ).…”
Section: Feasibility Of Controlmentioning
confidence: 99%